IMPLEMENTASI MODEL TGT BERBANTU MEDIA GAYANG SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR IPAS KELAS V SEKOLAH DASAR - Novia Kusumaningrum; Bambang Ismanto (STKIP Subang, 2023)
The importance of learning science in the world of basic education makes teachers required to be able to create a pleasant learning atmosphere and be able to motivate students to collaborate in the learning process. From the data in the field, the results of observations made by researchers during the pre-cycle on August 31, 2023 at Noborejo 01 Salatiga State Elementary School in the learning process using a classical model and centered on the teacher alone. solution to the application of the TGT (Teams Games Tournament) model with the help of gayang media as an increase in student learning outcomes. The existence of this TGT type cooperative learning model provides opportunities for students to be able to develop their thinking skills in solving problems and foster a spirit of learning and a sense of responsibility for fellow members in their group. The results of observations on the positive activities of students were 70% in cycle I and increased to 89% in cycle II, learning management was originally 72% in cycle I to 88% in cycle II, with the implementation of the TGT (Teams Games Tournament) cooperative model assisted by Gayang media (Puppet Pictures) the learning outcomes of students increased, this was shown from an average of 70.0 in cycle I to 77.8 in cycle II. As well as an increase in students' learning completeness from 69% in cycle I to 86% in cycle II.